Shape-stabilized phase change heat storage material based on bionic polymerization technology and preparation method of shape-stabilized phase change heat storage material
Through bionic polymerization technology, polydopamine cover layer is formed on the surface of copper oxide colloid particles and copper nanoparticles are generated, which solves the problem of insufficient load and thermal conductivity of fixed phase change heat storage materials prepared by traditional porous material carriers, and achieves high energy storage density and thermal conductivity of fixed phase change heat storage material.
Patent Information
- Application Number
- CN202411565320.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The fixed phase change heat storage materials prepared by traditional porous material support have problems such as low loading and poor thermal conductivity, which limits their wide application.
Through bionic polymerization technology, a polydopamine cover layer is formed on the surface of copper oxide colloidal particles, and interconnected pores are formed inside it. The copper ions are then reduced to copper nanoparticles to form copper nanoparticles doped with three-dimensional porous polydopamine, which is prepared as a carrier. A fixed phase change heat storage material with high load capacity and high thermal conductivity.
The energy storage density and thermal conductivity of fixed-phase change heat storage materials have been improved, and their application potential in the fields of solar energy storage and utilization, industrial waste heat utilization and building energy conservation have been enhanced.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of environmental protection and energy conservation, and in particular relates to a shaped phase-change heat storage material based on bionic polymerization technology and a preparation method thereof. Technical Background
[0002] With the rapid development of economy, the energy shortage problem is becoming increasingly serious. The development and utilization of renewable energy and the improvement of energy efficiency have become the focus of global attention. Phase change materials have attracted more and more attention due to their advantages such as high energy storage density, reusability and good stability. They are widely used in solar thermal systems, building energy conservation, industrial waste heat utilization and other fields, playing an important role in carbon emission reduction.
[0003] According to the different chemical compositions, phase change heat storage materials can be divided into two categories: organic and inorganic. Among them, organic phase change heat storage materials are the most promising phase change heat storage materials at present because of their advantages such as good chemical stability and thermal stability, low price, and no phase separation phenomenon. However, the direct use of organic phase change heat storage materials has problems such as low thermal conductivity and easy leakage of liquid phase during phase change, which limits their wide application. In order to solve the above problems, porous materials can be used as carriers to prepare shaped phase change heat storage materials by physical adsorption, vacuum infiltration, melt blending and other methods. So far, a large number of porous materials such as porous silicon, porous carbon, porous mineral materials, porous ceramics, zeolite molecular sieves, etc. have been used in the preparation of shaped phase change heat storage materials, and rich research results have been achieved. However, the use of traditional porous materials as carriers to prepare shaped phase change heat storage materials still has the following problems: ① The low loading leads to a low energy storage density of the phase change heat storage material; ② The poor thermal conductivity leads to low heat storage and release efficiency of the phase change heat storage material. These problems limit the wide application of shaped phase change heat storage materials. Summary of the invention
[0004] In order to improve the load and thermal conductivity of the shaped phase-change heat storage material, the present invention first prepares a stable suspension of copper hydroxide colloidal particles, and then forms a polydopamine coating on the surface of the copper oxide colloidal particles through biomimetic polymerization, and at the same time, the polydopamines form a mutually cross-linked three-dimensional network structure through polymerization reaction, and then dilute hydrochloric acid is added to the suspension to dissolve the copper hydroxide colloid to release copper ions, and form interconnected channels inside the polydopamine. At the same time, since the catechol in the polydopamine molecule has a strong chelating effect on metal ions, it is possible to fix the copper ions on its surface by adsorption to form a uniform copper ion coating. On this basis, a reducing agent is added to the solution, and the copper ions are reduced to copper nanoparticles using a simple in-situ reduction technique to obtain copper nanoparticles doped with three-dimensional porous polydopamine, and then a shaped phase-change heat storage material with high load and high thermal conductivity is prepared using it as a carrier.
[0005] On the one hand, the present invention provides a phase change heat storage material based on biomimetic polymerization technology, wherein the phase change heat storage material is a shaped phase change heat storage material of copper nanoparticles doped with three-dimensional porous polydopamine, and calculated by weight percentage, the phase change heat storage material based on biomimetic polymerization technology comprises the following components:
[0006] Carrier 5%-40%
[0007] Shaped phase change thermal storage material core material 60%-95%
[0008] Among them, the carrier is nanoparticle-doped three-dimensional porous polydopamine; the core material of the shaped phase change heat storage material is selected from one of stearic acid, myristic acid or polyethylene glycol, preferably stearic acid.
[0009] On the other hand, the present invention provides a method for preparing a phase change thermal storage material based on biomimetic polymerization technology, the preparation method comprising:
[0010] 1) preparing a stable suspension of copper hydroxide colloidal particles;
[0011] 2) adding the dopamine aqueous solution to the copper hydroxide colloidal particle stable suspension in step 1), incubating, and polymerizing the dopamine on the surface of the copper hydroxide colloidal particles to form a cross-linked polydopamine covering layer;
[0012] 3) adding dilute hydrochloric acid dropwise to the solution obtained in step 2), the copper hydroxide colloid dissolves and releases copper ions, and the copper ions are adsorbed on the surface of polydopamine;
[0013] 4) adding a reducing agent to the solution obtained in step 3), reducing the copper ions to copper nanoparticles, filtering and dehydrating the copper nanoparticles, and washing with distilled water to obtain copper nanoparticle-doped three-dimensional porous polydopamine;
[0014] 5) Copper nanoparticles are doped with three-dimensional porous polydopamine and stearic acid, placed in a vacuumable glass container, and then heated to melt the stearic acid, and the copper nanoparticles doped with three-dimensional porous polydopamine are completely immersed in the liquid stearic acid by shaking; impregnation is performed to make the carrier copper nanoparticles doped with three-dimensional porous polydopamine adsorbed saturatedly; the copper nanoparticles doped with three-dimensional porous polydopamine in a saturated adsorption state are taken out and dried, and when stearic acid no longer precipitates, a shaped phase change heat storage material of copper nanoparticles doped with three-dimensional porous polydopamine is obtained.
[0015] Preferably, the method for preparing the stable suspension of copper hydroxide colloidal particles in step 1) comprises dripping a cupric chloride solution into boiling water dropwise, stopping heating when the suspension turns dark blue, and obtaining a copper hydroxide colloidal suspension after cooling.
[0016] As further preferred, the concentration of the copper chloride solution in step 1) is 100 g / L-320 g / L, preferably 300 g / L.
[0017] Preferably, the concentration of dopamine in step 2) is 10 g / L-30 g / L, preferably 20 g / L.
[0018] Preferably, in step 2), the volume ratio of dopamine to the copper hydroxide colloidal particle stable suspension is 3:1-5:1, preferably 4:1.
[0019] Preferably, the concentration of dilute hydrochloric acid in step 3) is 0.3-0.6M, preferably 0.5M.
[0020] Preferably, the volume ratio of the dilute hydrochloric acid in step 3) to the solution obtained in step 2) is 1:2-1:4, preferably 1:2.5.
[0021] Preferably, the reducing agent in step 4) is glucose.
[0022] Preferably, the weight-to-volume ratio g / ml of the reducing agent in step 4) to the solution obtained in step 3) is 1:2-1:5, preferably 1:3.5.
[0023] Preferably, the temperature for heating to melt the stearic acid in step 5) is 80°C-98°C, preferably 90°C.
[0024] Preferably, the drying temperature in step 5) is 80°C-98°C, preferably 90°C.
[0025] On the other hand, the present invention provides an application of a phase change heat storage material based on bionic polymerization technology, which can be used for solar energy storage and utilization, industrial waste heat utilization, building energy conservation, etc.
[0026] The phase change heat storage material based on biomimetic polymerization technology of the present invention has the following advantages:
[0027] (1) The three-dimensional porous polydopamine prepared by the biomimetic polymerization method has a high loading capacity on the core material of the phase change material, which can improve the energy storage density of the shaped phase change heat storage material prepared with the three-dimensional porous polydopamine as the carrier;
[0028] (2) The biomimetic polymerization preparation method has the advantages of simple operation, mild conditions, and environmental friendliness;
[0029] (3) Copper nanoparticles are synthesized on the surface of three-dimensional porous polydopamine by an in-situ reduction method. The copper nanoparticles synthesized by this method can be firmly and tightly combined with polydopamine, which can effectively reduce the surface thermal resistance between the copper nanoparticles and polydopamine, improve the thermal conductivity, and prevent the deposition of copper nanoparticles during the phase change of the fixed phase change thermal storage material, thereby improving its dispersion stability and enhancing the thermal conductivity of the fixed phase change thermal storage material.
[0030] (4) The phase change heat storage material of the present invention has high energy storage density and good thermal conductivity, and can be used for solar energy storage and utilization, making a positive contribution to the realization of the country's important strategic goals of "carbon peak" and "carbon neutrality". DETAILED DESCRIPTION
[0031] The following examples are used to further illustrate the present invention; however, they are not intended to limit or define the scope of the present invention.
[0032] Example 1 Preparation of copper nanoparticles doped three-dimensional porous polydopamine
[0033] 1) Prepare a cupric chloride solution by adding 15 g of CuCl2·2H2O to 50 ml of distilled water;
[0034] 2) adding the copper chloride solution in step 1) dropwise into boiling water, stopping heating when the suspension turns dark blue, and obtaining a copper hydroxide colloidal suspension after cooling;
[0035] 3) adding 200 ml of 20 g / L dopamine distilled water solution to the copper hydroxide colloidal suspension in step 2) above, incubating for 48 hours, and allowing dopamine to polymerize on the surface of the copper hydroxide colloidal particles to form a cross-linked polydopamine covering layer;
[0036] 4) adding 100 ml of 0.5 M dilute hydrochloric acid to the suspension in step 3) above, the copper hydroxide colloid dissolves and releases copper ions, which are adsorbed on the surface of polydopamine;
[0037] 5) adding 10 g of a reducing agent (such as glucose, propyl formate, etc.) to the suspension in step 4) above, stirring for 10 min and incubating for 24 h, the copper ions are reduced to copper nanoparticles and then filtered and dehydrated, washed with distilled water 5 times and vacuum dried at 45° C. for 24 h, to obtain 4.5 g of copper nanoparticle-doped three-dimensional porous polydopamine (labeled as Poro-Cu-Dop);
[0038] According to the test, the specific surface area of Poro-Cu-Dop can reach 417.24m 2 / g, has good adsorption and fixation ability for new phase change materials;
[0039] Example 2 Preparation of copper nanoparticle-doped three-dimensional porous polydopamine shaped phase change heat storage material
[0040] 1) Place 50 g of stearic acid and 0.5 g of Poro-Cu-Dop in a custom-made vacuum glass container, evacuate the container using a vacuum pump and keep the container evacuated for 30 min;
[0041] 2) Heat to 90°C to melt the stearic acid, and oscillate to completely immerse Poro-Cu-Dop in the liquid stearic acid;
[0042] 3) Vacuum impregnation for 2 h to saturate the carrier with adsorption;
[0043] 4) The Poro-Cu-Dop in the saturated adsorption state was taken out, transferred to a drying oven, and dried at 90°C for 4 hours. When stearic acid no longer precipitated, 7.4 g of copper nanoparticle-doped three-dimensional porous polydopamine shaped phase change thermal storage material (labeled as SA / Poro-Cu-Dop) was obtained;
[0044] According to the test, the loading amount of stearic acid in SA / Poro-Cu-Dop can reach 93.28%, the melting and solidification phase change enthalpies of SA / Poro-Cu-Dop are 194.89 J / g and 208.51 J / g respectively, and its thermal conductivity is 0.605 W / m·K.
[0045] For comparison, polydopamine particles were synthesized without the copper hydroxide colloidal particle template, and the polydopamine particles were used as a carrier to fix stearic acid to prepare a polydopamine particle fixed phase change heat storage material. The comparison example is as follows:
[0046] Comparative Example 1 Preparation of polydopamine particles
[0047] 1) Prepare a cupric chloride solution by adding 15 g of CuCl2·2H2O to 50 ml of distilled water;
[0048] 2) adding the copper chloride solution in step 1) dropwise into boiling water, stopping heating when the suspension turns dark blue, and obtaining a copper hydroxide colloidal suspension after cooling;
[0049] 3) filtering the copper hydroxide colloid suspension in step 2) to remove the copper hydroxide colloid and obtain a filtrate free of copper hydroxide colloid;
[0050] 4) adding 200 ml of 20 g / L dopamine distilled water solution to the filtrate in step 3) above, incubating for 48 h with stirring, so that dopamine polymerizes to form polydopamine particles;
[0051] 5) The mixed solution in step 3) was centrifuged to separate the solid and liquid, and the polydopamine particles were washed three times with distilled water, and then placed in a vacuum drying oven and vacuum dried at 45°C for 24 hours to obtain 1.7 g of polydopamine particles (labeled as: Poly-Dop); after testing, the specific surface area of the particles was 11.72 m 2 / g.
[0052] Comparative Example 2 Polydopamine particle shaped phase change heat storage material
[0053] 1) Place 50 g of stearic acid and 0.5 g of Poly-Dop in a custom-made vacuum glass container, evacuate the container using a vacuum pump and keep the container evacuated for 30 min;
[0054] 2) Heat to 90°C to melt the stearic acid, and oscillate to fully immerse the Poly-Dop in the liquid stearic acid;
[0055] 3) Vacuum impregnation for 2 h to saturate the carrier with adsorption;
[0056] 4) The Poly-Dop in the saturated adsorption state was taken out, transferred to a drying oven, and dried at 90° C. for 4 h. When stearic acid no longer precipitated, 1.8 g of polydopamine particle-shaped phase change thermal storage material (labeled as SA / Poly-Dop) was obtained;
[0057] According to the test, the loading amount of stearic acid in SA / Poly-Dop is 73.04%, the melting and solidification phase change enthalpies of SA / Poly-Dop are 132.66 J / g and 143.40 J / g respectively, and its thermal conductivity is 0.291 W / m·K.
[0058] It can be found from the above comparative examples that the copper nanoparticle-doped three-dimensional porous polydopamine shaped phase change heat storage material prepared by the present invention greatly improves the loading capacity and phase change enthalpy of the shaped phase change heat storage material due to the synthesis of the three-dimensional porous polydopamine, and greatly improves the thermal conductivity of the shaped phase change heat storage material due to the in-situ generation of copper nanoparticles on the surface of the three-dimensional porous polydopamine.
[0059] For comparison, a three-dimensional porous polydopamine without copper nanoparticle doping was synthesized and used as a carrier to fix stearic acid to prepare a three-dimensional porous polydopamine shaped phase change heat storage material. The comparison example is as follows:
[0060] Comparative Example 3 Preparation of three-dimensional porous polydopamine
[0061] 1) Prepare a cupric chloride solution by adding 15 g of CuCl2·2H2O to 50 ml of distilled water;
[0062] 2) Add the copper chloride solution drop by drop into boiling water. When the suspension turns dark blue, stop heating and cool it to obtain a copper hydroxide colloidal suspension.
[0063] 3) adding 200 ml of 20 g / L dopamine distilled water solution to the copper hydroxide colloidal suspension and incubating for 48 hours, so that dopamine polymerizes on the surface of the copper hydroxide colloidal particles to form a cross-linked polydopamine covering layer;
[0064] 4) 100 ml of 0.5 M dilute hydrochloric acid was added to the above suspension to dissolve the copper hydroxide colloid. The solid-liquid separation was achieved by filtration, and the solid phase was washed 5 times with distilled water, and then vacuum dried at 45°C for 24 hours to obtain 1.6 g of three-dimensional porous polydopamine (labeled as Poro-Dop1). After testing, the specific surface area of Poro-Dop1 can reach 439.50 m 2 / g.
[0065] Comparative Example 4 Three-dimensional porous polydopamine shaped phase change heat storage material
[0066] 1) Place 50 g of stearic acid and 0.5 g of Poro-Dop1 in a custom-made vacuum glass container, evacuate the container using a vacuum pump and keep the container evacuated for 30 min;
[0067] 2) Heat to 90°C to melt the stearic acid, and oscillate to completely immerse Poro-Dop1 in the liquid stearic acid;
[0068] 3) Vacuum impregnation for 2 h to saturate the carrier with adsorption;
[0069] 4) Poro-Dop1 in a saturated adsorption state was taken out, transferred to a drying oven, and dried at 90°C for 4 h. When stearic acid no longer precipitated, 7.9 g of a three-dimensional porous polydopamine shaped phase change thermal storage material (labeled as SA / Poro-Dop1) was obtained;
[0070] According to the test, the loading amount of stearic acid in SA / Poro-Dop1 can reach 93.74%, the melting and solidification phase change enthalpies of SA / Poro-Dop1 are 195.02 J / g and 208.73 J / g respectively, and its thermal conductivity is 0.260 W / m·K.
[0071] From the above comparative examples, it can be found that when no copper nanoparticles are generated, the loading amount and phase change enthalpy of SA / Poro-Dop1 are not much different from those of SA / Poro-Cu-Dop, but the thermal conductivity of SA / Poro-Dop1 is greatly reduced; when copper nanoparticles are generated, the thermal conductivity of SA / Poro-Cu-Dop is increased by 132.7% compared with the thermal conductivity of SA / Poro-Dop1. Therefore, in the present invention, the in-situ generation of copper nanoparticles on the surface of three-dimensional porous polydopamine plays an important role in improving the thermal conductivity of the shaped phase change heat storage material.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A phase change heat storage material based on biomimetic polymerization technology, characterized in that The phase-change heat storage material is a shaped phase-change heat storage material of copper nanoparticles doped with three-dimensional porous polydopamine. Calculated by weight percentage, the phase-change heat storage material based on biomimetic polymerization technology includes the following components: Carrier 5%-40% Shaped phase change thermal storage material core material 60%-95% Among them, the carrier is nanoparticle-doped three-dimensional porous polydopamine; the core material of the shaped phase change heat storage material is selected from one of stearic acid, myristic acid or polyethylene glycol, preferably stearic acid.
2. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 1, characterized in that The preparation method comprises: 1) preparing a stable suspension of copper hydroxide colloidal particles; 2) adding the dopamine aqueous solution to the copper hydroxide colloidal particle stable suspension in step 1), incubating, and polymerizing the dopamine on the surface of the copper hydroxide colloidal particles to form a cross-linked polydopamine covering layer; 3) adding dilute hydrochloric acid dropwise to the solution obtained in step 2), the copper hydroxide colloid dissolves and releases copper ions, and the copper ions are adsorbed on the surface of polydopamine; 4) adding a reducing agent to the solution obtained in step 3), reducing the copper ions to copper nanoparticles, filtering and dehydrating the copper nanoparticles, and washing with distilled water to obtain copper nanoparticle-doped three-dimensional porous polydopamine; 5) Copper nanoparticles are doped with three-dimensional porous polydopamine and stearic acid, placed in a vacuumable glass container, and evacuated, heated until the stearic acid melts, and the copper nanoparticles doped with three-dimensional porous polydopamine are completely immersed in the liquid stearic acid by shaking; impregnation is performed to make the carrier copper nanoparticles doped with three-dimensional porous polydopamine adsorbed saturatedly; the copper nanoparticles doped with three-dimensional porous polydopamine in a saturated adsorption state are taken out and dried, and when stearic acid no longer precipitates, the copper nanoparticles doped with three-dimensional porous polydopamine are obtained. Steady phase change heat storage material.
3. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 2, characterized in that The method for preparing the stable suspension of copper hydroxide colloidal particles in step 1) comprises dripping a cupric chloride solution into boiling water drop by drop, stopping heating when the suspension turns dark blue, and obtaining the copper hydroxide colloidal suspension after cooling.
4. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 3, characterized in that: The concentration of the copper chloride solution in step 1) is 100 g / L-320 g / L, preferably 300 g / L.
5. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 2, characterized in that The concentration of dopamine in step 2) is 10 g / L-30 g / L, preferably 20 g / L; the volume ratio of dopamine to the copper hydroxide colloidal particle stable suspension in step 2) is 3:1-5:1, preferably 4:
1.
6. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 2, characterized in that The concentration of the dilute hydrochloric acid in step 3) is 0.3-0.6M, preferably 0.5M; the volume ratio of the dilute hydrochloric acid in step 3) to the solution obtained in step 2) is 1:2-1:4, preferably 1:2.
5.
7. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 2, characterized in that Preferably, the reducing agent in step 4) is glucose; the weight-to-volume ratio (g / ml) of the reducing agent in step 4) to the solution obtained in step 3) is 1:2-1:5, preferably 1:3.
5.
8. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 2, characterized in that In the step 5), the temperature at which the stearic acid is heated to melt is 80° C.-98° C., preferably 90° C.
9. The method for preparing a phase change thermal storage material based on biomimetic polymerization technology according to claim 2, characterized in that The drying temperature in step 5) is 80°C-98°C, preferably 90°C.
10. The application of a phase change heat storage material based on biomimetic polymerization technology as claimed in claim 1, wherein the application is in the field of solar energy storage and utilization, industrial waste heat utilization or building energy conservation.
Citation Information
Patent Citations
Preparation method of high-thermal-conductivity composite phase-change material
CN110129010A
Method for preparing carbon-sphere-based composite phase-change material
CN110305634A
Preparation method of shape-stabilized phase change material
CN110527493A
Preparation method of composite phase change material
CN110527495A
Phase-change micro-capsule with full-wave-band photo-thermal conversion function and preparation method thereof
CN112251197A